Nocturnal Excretion in Healthy Older Women and Rationale for a Safer Approach to Sleep Disruption. Issue 12 (22nd August 2019) - Tyagi, Shachi; Perera, Subashan; Clarkson, Becky D.; Tadic, Stasa D.; Resnick, Neil M.
Abstract : OBJECTIVES: Insomnia, especially difficulty maintaining sleep, is prevalent among older adults and increases the incidence of falls and fractures. Moreover, the drugs used to treat it exacerbate the risk. Yet current therapies fail to address one of its most common causes in older adults: nocturia and its primary contributor, nocturnal polyuria (NP), especially among the majority of individuals without lower urinary tract symptoms (LUTS). Therefore, we examined the factors associated with nocturia in two groups of such older women and the impact of nocturia on sleep. DESIGN: Secondary analysis of two observational studies of bladder function in carefully evaluated healthy older women. SETTING: Academic medical center. PARTICIPANTS: A total of 39 women without LUTS who had adequate fluid intake (ie, >1200 mL urine output/24 h recorded on their diary), normal videourodynamic testing, and normal daytime frequency (≤7 voids). MEASUREMENTS: Voided volumes and sleep duration obtained from subjects' 3‐day voiding diary, and sleep quality from the Center for Epidemiologic Studies Depression Scale. Nighttime excretion of more than 33% of 24‐hour urine volume was considered NP. RESULTS: Overall, 21 of these healthy subjects (54%) awakened at least once nightly to void, and 19 (90%) of them had NP. Compared with those without nocturia, participants with nocturia had shorter duration of the first uninterrupted sleep period (182 ± 100 vs 250 ± 60 min; P = .03), and they reported worse sleep quality. Two factors contributed independently to nocturia: (1) a larger proportion of 24‐hour urine output at night (43.4 ± 7.4% vs 25.4 ± 5.5%; P = <.001) and (2) smaller bladder capacity (484 ± 157 mL vs 608 ± 167 mL; P = .02). CONCLUSIONS: Nocturia, NP, and reduced bladder capacity are very common even in healthy older women without LUTS and are associated with impaired sleep. Thus applying currently available modalities to address both NP and reduced bladder capacity may effectively treat sleep disruption without incurring the complications of sedative‐hypnotics. J Am Geriatr Soc 67:2610–2614, 2019